The impact of alternative childcare policies on mothers' employment for selected EU countries - Edlira Narazani; Ana Agúndez García; Michael Christl; Francesco Figari (European Commission, Joint Research Centre (JRC), 2022)
The Barcelona targets on childcare help increase women's labour-market participation and close the gender employment gap by enhancing the provision of early childhood education and care. To contribute to the debate on the revision of the targets, this paper estimates the impact on labour par- ticipation of mothers of alternative scenarios of formal childcare policies for a number of countries. The selected countries (IT, EE, IE, AT, HU, FI, PT, PL) represent different female participation in the labour market and childcare systems. The analysis makes use of the EUROLAB and EU- ROMOD models, based on EU-SILC data, to estimate female labour supply reactions to childcare reforms. Furthermore, EUROLAB allows us to also account for the labour demand side. The first reforms analyzed consist in providing formal childcare to 40%, 50%, 60% and 65% of children under 3. Our results show that the achievement of these levels of childcare (through increases in childcare availability and usage) would lead to significant increases in the labour supply of mothers (at the extensive and intensive margins), especially in countries where the current labour participa- tion of women and the share of formal childcare is low. Accounting for labour demand, we show that the expected final employment effects in the new labour market equilibrium will be less pro- nounced, but still positive. Additionally, we analyse a pricing policy consisting in free childcare, showing that this policy would be most effective to support mothers' labour market participation in countries where childcare fees are relatively high.
Keywords: J20; J22; J23; J13; 330; Labour market equilibrium; labour supply; labour demand; behavioural models; discrete choice; childcare